The Effect of Different Magnesium Sources on Renal Magnesium Transporters in Rats Fed a High Fat Diet - Şahin, Kazım; Yazgan, Kubra; Tuzcu, Mehmet; Orhan, Cemal; Şahin, Nurhan; Ojalvo, Sara; Komorowski, James (Wiley, 2020)
[Abstract Not Available]
Annual Meeting on Experimental Biology -- APR 04-07, 2020 -- San Diego, CA